Determination of four residual solvents in cefepime by headspace gas chromatography - Le Wang (Results in Chemistry, 2024)
Objective: To establish a headspace gas chromatography method to determine the residual solvents of methanol, acetone, dichloromethane, and toluene in cefepime. Methods: Headspace gas chromatography using a DB-624 capillary column and temperature program was performed to detect four residual solvents in cefepime. The temperature program consisted of an initial temperature of 60 ℃maintained for 4 min, a temperature increased to 120 ℃ at 20 ℃·min−1 maintained for 3 min, and then a temperature increased to 200 ℃ at 40 ℃·min−1 maintained for 3 min. Results: Linear relationships were found between the peak areas and mass concentrations of the four solvents mentioned above within the defined ranges. The limits of detection for methanol, acetone, dichloromethane and toluene were 0.50, 0.15, 0.10 and 0.08 mg·L-1, respectively. The recoveries obtained using the standard addition method ranged from 98.41 % to 100.94 %. Conclusion: This method demonstrated high sensitivity and good reproducibility, and it can be used to effectively control the residual amounts of methanol, acetone, dichloromethane, and toluene, to further improve the quality of cefepime.